IDENTIFIKASI TEMATIK AUN SEBAGAI IMPLEMENTASI SDGS NO 4 DI PENDIDIKAN TINGGI ASEAN - Alwirasesa Rumbo Sitepu, Ryando; Pratama Nurratri, Januari (Penerbit Lafadz Jaya, 2025)
The ASEAN University Network (AUN) is a collaborative platform for higher education institutions in Southeast Asia, aimed at enhancing the quality of human resources through educational institutions by fostering collaboration among universities within the ASEAN region. This study seeks to analyze the role of the ASEAN University Network (AUN) as an actor in promoting the implementation of Sustainable Development Goal (SDG) 4 among AUN Core Member universities, through a series of thematic programs designed by the AUN. SDG 4, which emphasizes quality education, is a key priority of sustainable development that necessitates cross-national collaboration. This research employs a descriptive qualitative approach, with data collected through literature reviews and document analysis of AUN policy materials. The findings reveal that the AUN has launched thematic programs that actively contribute to achieving the targets of SDG 4. The study identifies a strong alignment between AUN's thematic initiatives and SDG targets 4.3 through 4.B, both in terms of conceptual understanding and practical implementation. These are realized through efforts such as strengthening quality assurance mechanisms, preparing the ASEAN youth, and addressing disparities in educational access. This research underscores the significance of AUN as a vital intermediary in higher education, playing a strategic role in advancing the achievement of SDG 4 in the ASEAN region.